2016
DOI: 10.1039/c6cp04948f
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns and structural motifs of cadmium clusters with up to 60 atoms: disordered or not?

Abstract: Using two different approaches, the structures of Cd clusters are optimized. At first, parameterized density-functional calculations using the DFTB method in combination with evolutionary algorithms provide one set of candidate structures. Second, earlier proposed structures based on the Gupta potential provide a second set. Subsequently, all structures of each set are re-optimized using parameter-free density-functional calculations. It turned out that those based on the DFTB calculations in almost all cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…1, a bulk Cd structure constructed by metallic bonding of atoms to each other forms a hexagonal-close package structure that belongs to the space group of P 6 3 / mmc and the point group of D 6h . 19 Using total energy calculations, lattice parameters for the bulk structure are found to be a = b = 2.98 Å and c = 5.75 Å. However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1, a bulk Cd structure constructed by metallic bonding of atoms to each other forms a hexagonal-close package structure that belongs to the space group of P 6 3 / mmc and the point group of D 6h . 19 Using total energy calculations, lattice parameters for the bulk structure are found to be a = b = 2.98 Å and c = 5.75 Å. However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…17 While Alvarez et al showed that metallicity of Cd n clusters emerges as a result of sp-hybridization, 18 and a study by Kohaut et al revealed that such clusters do not show metallic properties up to n = 60. 19 Besides, Oyeniyi et al developed and used a method to calculate the electronic excitation energies and absorption spectra of zero dimensional Zn, Cd and S clusters. 20 Xie et al demonstrated that nanoribbons of CdTe with their large photoresponse and high gain to visible NIR irradiation are promising candidates for photodetection applications.…”
Section: Introductionmentioning
confidence: 99%
“…As Cd is a group XII metal with a closed-shell electronic configuration, cadmium clusters are also considered to be ideal model systems to study the nature of the insulatorto-metal transition that must occur along the path bridging the dimer with the bulk limit 2 . However, the problem of characterizing the structure of cadmium clusters has been addressed only in a very limited number of computational works [3][4][5][6][7][8][9][10] , which moreover do not generally agree in the proposed global minimum (GM) structures. Experimental results about relative stabilities of charged cadmium clusters are also available [11][12][13] , which have not yet been convincingly reproduced and interpreted.…”
Section: Introductionmentioning
confidence: 99%